PEMBUATAN MEDIA PEMBELAJARAN BIOLOGI SEKOLAH MENENGAH TINGKAT PERTAMA - Wijayanto, Buyung Aji; Sumirat, Estiarto Wahyu (Speed - Sentra Penelitian Engineering dan Edukasi, 2009)
The growth of computer technolodi not only used for word prossesor it is also for learn multimedia that make possible for student college to make design for scienes. Now there many institution of education used the growth of computer technologi to make tutorial for education. But only a few people make tutorial that used Indonesian language it just a picture that difficult to understand. The goal from this reserch is to make tutorial biologi for SLTP that can acsses online and can be downloaded. Benefit from this research are to help the student and the teacher for easy and effective to learn and also its can be accses even can download online and offline. Reserch from this method in use is Reference Method, Observation, Interview, Experiment this method included anlysed, design and implementation.The result of this reserch are to make biology tutorial are specially in biology such as blood,breath, with Indonesian language,sounds,and image that as same as with curriculum for SLTP classÂ  VIII in CD/DVD so it can use for learn by itself.